Corkscrew collaterals in atherosclerosis obliterans. Issue 12 (16th October 2017) - Fujii, Yuichi; Ueda, Tomohiro; Uchimura, Yuko; Teragawa, Hiroki
Key Clinical Message: Marked calcifications in the femoral artery obscured imaging of the artery in computed tomography (CT) and duplex ultrasonography. The presence of corkscrew collateral arteries in patients with Atherosclerosis obliterans (ASO) indicates total artery occlusion. Abstract : Marked calcifications in the femoral artery obscured imaging of the artery in computed tomography (CT) and duplex ultrasonography. The presence of corkscrew collateral arteries in patients with Atherosclerosis obliterans (ASO) indicates total artery occlusion.